Game User Experience Evaluation - Bernhaupt, Regina (Human-Computer Interaction Series,, 2015)
Evaluating interactive systems for their user experience (UX) is a standard approach in industry and research today. This book explores the areas of game design and development and Human Computer Interaction (HCI) as ways to understand the various contributing aspects of the overall gaming experience. Fully updated, extended and revised this book is based upon the original publication Evaluating User Experience in Games, and provides updated methods and approaches ranging from user- orientated methods to game specific approaches. New and emerging methods and areas explored include physiologically- orientated UX evaluation, user behaviour, telemetry based methods and social play as effective evaluation techniques for gaming design and evolving user-experience. Game User Experience Evaluation allows researchers, PhD students as well as game designers and developers to get an overview on available methods for all stages of the development life cycle.